2004
DOI: 10.1093/ndt/gfh539
|View full text |Cite
|
Sign up to set email alerts
|

L-2-Oxothiazolidine-4-carboxylic acid reduces in vitro cytotoxicity of glucose degradation products

Abstract: The GDP-induced stimulation of free radicals in mesothelial cells in the present study may provide a possible mechanism of GDP cytotoxicity. Because OTZ reduced the toxic effects of GDP on mesothelial cells, this compound may improve biocompatibility of peritoneal dialysis fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Peritoneal fluid bioincompatibility resulting from the presence of GDPs is one of main factors contributing to dialysis failure and loss of peritoneum in CAPD patients [7,8,9,10,11,12,13]. Several attempts have been developed to improve PD fluid biocompatibility through eliminating, minimizing or at least trapping GDPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Peritoneal fluid bioincompatibility resulting from the presence of GDPs is one of main factors contributing to dialysis failure and loss of peritoneum in CAPD patients [7,8,9,10,11,12,13]. Several attempts have been developed to improve PD fluid biocompatibility through eliminating, minimizing or at least trapping GDPs.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is the ability of carnosine to quench reactive aldehydes such as acetaldehydes, formaldehyde, malondialdehyde (MDA), hydroxyalkenals and others [27, 29]. Many of these aldehydes are present in the heat-sterilized PDF, and other aldehydes like MDA and hydroxyalkenals are elaborated during incubation of HPMC with GDPs [11, 38]. Accordingly, the preventive effect of carnosine of HPMC protein modification may be related to the carnosine reaction with both GDPs present in dialysis fluid and the aldehydes generated as a result of cellular oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morgan et al showed that various GDPs delay remesothelization of peritoneum in a scratch wound model of peritoneal repair and documented that the effect of GDPs was independent of the presence of glucose [37]. Breborowicz et al have shown that L-2-oxothiazolidine-4-carboxylic acid (a precursor for glutathione), reduces the GDP-induced stimulation of free radicals cytotoxicity of GDPs in human peritoneal mesothelial cells and argued that addition of L-2-oxothiazolidine-4-carboxylic acid in PDF may improve biocompatibility of PDF [38].…”
Section: Role Of Glucose Degradation Products (Gdps)mentioning
confidence: 99%